A Misbehavior Node Detection Algorithm for 6LoWPAN Wireless Sensor Networks - La, Vinh Hoa; Cavalli, Ana R. (Proceedings - International Conference on Distributed Computing Systems Workshops, 2016)
In the current era, Wireless Sensor Networks (WSNs) and Internet of Things (IoT) have been considered as two very attractive subjects in both industry and research community. The resource-constraint characteristics of physical objects in those networks presumably limit the secure design and development of security protocols. Whilst, sensor nodes which usually operate in unattended and even harsh environments, are prone to failures and malicious attacks. Misbehavior node detection is therefore an important issue to assure quick recovery and reliable functioning of the networks. In this paper, we present a misbehavior node detection algorithm using weighted-link in a hierarchical 6LoWPAN (IPv6 over Low power Wireless Personal Area Networks) sensor network. We also evaluate the algorithm by a number of experiments over a real testbed.